STUDY OF VULGAR TEXT AND ILUSTRASI ON T-SHIRT - Ari, Ida Ayu Dwita Krisna; Fajaraditya Setiawan, I Nyoman Anom (Jurnal Bahasa Rupa, 2019)
Brand new produce lifestyle support products, t-shirt products popping up fertile. The high competition in the clothing company industry causes, the product is demanded to have an appeal as a differentiator with other products. Some clothing companies have unique concepts, such as text or illustrations that are vulgar and even classified as taboo to say. The paradigm, making research on vulgar themed t-shirts need to a studied at an aesthetic level. Providing valuable input to the academic studies and clothing business. Qualitatively qualitative analysis, social phenomena in society as objects and the interesting reality of characteristics, signs or descriptions of the existing situation and phenomenon conditions. Prizes in the form of t-shirts with vulgar themes, it is assumed that the audience's awareness of art, including the composition of the results of the interaction between memory perception and visual perception as well as the sense of comprehension of the user.